2010
DOI: 10.3342/ceo.2010.3.4.207
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Continuous Positive Airway Pressure Level in Korean Patients with Obstructive Sleep Apnea Syndrome

Abstract: ObjectivesThe aim of this study was to investigate optimal continuous positive airway pressure (CPAP) level, to examine the factors affecting optimal CPAP level, and to develop a predictive equation for optimal CPAP level in Korean patients with obstructive sleep apnea syndrome (OSAS).MethodsA total of 202 patients with OSAS who underwent successful manual titration for CPAP treatment were included in this study. Correlations between the optimal CPAP level and baseline data including anthropometric and polysom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 25 publications
2
21
1
1
Order By: Relevance
“…5,6,8,9,11 This finding is also compatible with our previous study, in which greater PnCPAP was required to suppress OSAS when a patient had higher AHI. 24 Of note, the present study demonstrated that the balance between the amount of oropharyngeal soft tissue and the craniofacial bony size could predict PnCPAP.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…5,6,8,9,11 This finding is also compatible with our previous study, in which greater PnCPAP was required to suppress OSAS when a patient had higher AHI. 24 Of note, the present study demonstrated that the balance between the amount of oropharyngeal soft tissue and the craniofacial bony size could predict PnCPAP.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, several equations incorporating these variables have been used to predict PnCPAP. [5][6][7][8][9][10][11][12] Although these equations cannot replace the use of proper manual titration to identify PnCPAP, such predictive equations are still useful for determination of the starting pressure of CPAP titration, thereby eliminating the need for frequent changes in pressure upper airway anatomical imbalance may be involved in the pathogenesis in OSAS. [17][18][19] This finding led us to hypothesize that the upper airway anatomical imbalance is more strongly correlated with PnCPAP than BMI in Japanese OSAS patients.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the studies, forty-six of them were potentially relevant and the full-text versions were downloaded for detailed evaluation [ 13 52 , 55 – 60 ] and four studies were identified after reading the references and they were also downloaded [ 60 – 64 ]. After detailed review of the fifty studies, the authors came to a consensus for twenty-six studies [ 13 15 , 19 , 20 , 31 , 32 , 34 , 35 , 38 , 43 45 , 47 51 , 55 – 61 , 63 , 64 ] which presented equations that met the inclusion and exclusion criteria (see Figure 1 ). There were 4,436 patients in the development phases and 3,489 patients in the validation phases for the combined studies included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous studies conducted to designate patients' CPAP pressure levels beforehand to avoid second-night stays and reduce long waiting times. In most of these studies, BMI and AHI were reported to be the most important factors that affected CPAP pressure level and it was reported that optimal CPAP pressure level could be designated beforehand with formulas designed according to these values, enabling initiation of CPAP treatment with these pressure levels [23][24][25]. In these studies, the aim was to designate CPAP pressure level beforehand, according to the respiratory distress index (RDI), oxygen saturation (SaO 2 ), ESS, and BMI.…”
Section: Discussionmentioning
confidence: 99%